Potential of Analog Rice for Diabetes and Dyslipidemia: A Narrative Review of In Vivo Insight - Ariny Poespitasari; Fitriyono Ayustaningwarno; Ninik Rustanti (Media Publikasi Cendekia Indonesia, 2026)
Analog rice is a potential alternative staple food for managing degenerative diseases, particularly type 2 diabetes mellitus (T2DM) and dyslipidemia. It can be formulated from various raw materials, including tubers, cereals, legumes, pulses, vegetables, and fruits, resulting in a product that resembles white rice. It contains bioactive compounds at levels comparable to or higher than that of white rice. The bioactive compounds, such as dietary fiber and resistant starch, function to slow glucose absorption and promote beneficial SCFA production, while the phenolic compounds act as potent antioxidants that may protect tissues from oxidative damage induced by hyperglycemia and dyslipidemia. This narrative review utilized PubMed, Scopus, ScienceDirect, and Google Scholar with keywords including